Alteration in ventricular pressure stimulates cardiac repair and remodeling. (August 2019) - Unno, Kazumasa; Oikonomopoulos, Angelos; Fujikawa, Yusuke; Okuno, Yusuke; Narita, Singo; Kato, Tomohiro; Hayashida, Ryo; Kondo, Kazuhisa; Shibata, Rei; Murohara, Toyoaki; Yang, Yanfei; Dangwal, Seema; et al.
Abstract: The mammalian heart undergoes complex structural and functional remodeling to compensate for stresses such as pressure overload. While studies suggest that, at best, the adult mammalian heart is capable of very limited regeneration arising from the proliferation of existing cardiomyocytes, how myocardial stress affects endogenous cardiac regeneration or repair is unknown. To define the relationship between left ventricular afterload and cardiac repair, we induced left ventricle pressure overload in adult mice by constriction of the ascending aorta (AAC). One week following AAC, we normalized ventricular afterload in a subset of animals through removal of the aortic constriction (de-AAC). Subsequent monitoring of cardiomyocyte cell cycle activity via thymidine analog labeling revealed that an acute increase in ventricular afterload induced cardiomyocyte proliferation. Intriguingly, a release in ventricular overload (de-AAC) further increases cardiomyocyte proliferation. Following both AAC and de-AAC, thymidine analog-positive cardiomyocytes exhibited characteristics of newly generated cardiomyocytes, including single diploid nuclei and reduced cell size as compared to age-matched, sham-operated adult mouse myocytes. Notably, those smaller cardiomyocytes frequently resided alongside one another, consistent with local stimulation of cellular proliferation. Collectively, our data demonstrate that adult cardiomyocyte proliferation can be locally stimulated by an acute increase or decrease of ventricular pressure, and this mode of stimulation can be harnessed to promote cardiac repair. Graphical abstract: Ascending aortic constriction (AAC) triggers new cardiomyocyte formation due to LV pressure overload (middle panel). Relieving this pressure overload by de-banding or de-AAC (far right panel) further stimulates myocyte formation. Redox stress, secondary to LV pressure alteration, plays a critical role in this process.Unlabelled Image Highlights: LV pressure loading induces cardiomyocyte hypertrophy, and LV pressure unloading induces LV reverse remodeling with the return of hypertrophied cardiomyocytes toward normal size. In the process of LV reverse remodeling, the fraction of smaller cardiomyocytes increases. Smaller cardiomyocytes observed during LV reverse remodeling are characterized by single diploid nucleus, entry into the cell cycle, and expression of proliferation-related genes. Fate mapping shows that these cardiomyocytes originate from preexistent cardiomyocytes. Importantly, these newly generated cardiomyocytes can further develop into mature functional cardiomyocytes. Although, LV pressure overload can cue cell division, sustained pressure overload triggers oxidative stress, which adversely affects cardiomyocyte proliferation overtime. Relieving the LV pressure overload establishes the redox balance and triggers additional cardiomyocyte proliferation.